Synthesis And Characterization Of Tungsten Oxide_Zinc Oxide Hybrid Particles And Their Photocatalytic Study In Removal Of Rhb Dye - Saharuddin, Nur Atiqah (Universiti Sains Malaysia, 2017)
There are widely research has been done on the photocatalytic performance in organic dye removal. However, study regarding photodegradation mechanism by hybrid semiconductor photocatalysts with a narrow band gap core semiconductor coupled with a shell layer of wide band gap semiconductor is rarely explored by researchers. In this work, the WOx particles (narrow band gap semiconductor, 2.80 eV) were pre-synthesized using solution precipitation method. The XRD analysis shows that the particles composed of WO3 particles and WO2 particles (WOx, x = 2, 3). The poor emission efficiency of WOx particles at wavelength of 401 nm, 511 nm and 696 nm is expected in RTPL analysis as WOx is an indirect band gap semiconductor. As compared to annealed WOx particles (650°C for 4 hours), the unannealed WOx particles shows better photocatalytic activity with photodegradation efficiency of 27.60 % than annealed WOx with only 8.53 % under UV irradiation for 80 minutes. Subsequently, the unannealed WOx particles were immersed into zinc nitrate solution at required synthesis condition for the deposition of ZnO. The photocatalytic performances of these particles prepared using different (i) concentration of Zn nitrate tetrahydrate (0.08 M, 0.12 M, 0.50 M and 1.00 M) and (ii) deposition duration (4 hours, 24 hours, 48 hours and 72 hours), were studied. Generally, the photocatalytic performance of WOx particles under UV irradiation was retarded with the deposition of ZnO. However, it is noted that the increase of concentration of Zn nitrate tetrahydrate and deposition duration generally provided better photocatalytic activity for the hybrid particles. The scavenger test was performed on WOx – ZnO hybrid particles synthesized at 72 hours. The study suggests that the reactive species for RhB dye removal were electrons and OH- free radicals. Based on these findings, the photodegradation mechanisms of RhB dye by WOx – ZnO hybrid particles is proposed.